2002
DOI: 10.1099/00221287-148-6-1805
|View full text |Cite
|
Sign up to set email alerts
|

HPr kinase/phosphatase of Bacillus subtilis: expression of the gene and effects of mutations on enzyme activity, growth and carbon catabolite repression

Abstract: HPr kinase/phosphatase (HPrK/P) is the key protein in regulation of carbon metabolism in Bacillus subtilis and many other Gram-positive bacteria. Whether this enzyme acts as a kinase or phosphatase is determined by the nutrient status of the cell. Mutational analysis of residues in a Walker A box nucleotide-binding motif revealed that it is not only important for kinase but is also involved in phosphatase activity. In addition, a signature sequence specifically conserved among HPrK/P orthologues is required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 31 publications
7
55
0
Order By: Relevance
“…Such mutants have been obtained, for example, with B. subtilis (251,315,709), S. xylosus (357), and L. casei (198). In all three organisms, the inactivation of hprK causes a relief from CCR, but for several B. subtilis catabolic operons, the releasing effect in hprK mutants is markedly stronger than that in ptsH1 mutants (249,523,685).…”
Section: Role Of P-ser-hpr In Ccrmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mutants have been obtained, for example, with B. subtilis (251,315,709), S. xylosus (357), and L. casei (198). In all three organisms, the inactivation of hprK causes a relief from CCR, but for several B. subtilis catabolic operons, the releasing effect in hprK mutants is markedly stronger than that in ptsH1 mutants (249,523,685).…”
Section: Role Of P-ser-hpr In Ccrmentioning
confidence: 99%
“…The inhibitory effect of ATP was stronger at low Mg 2ϩ concentrations. Mutant studies with hprK from various organisms suggested that Walker motif A is important not only for the kinase but also for the phosphorylase function (315,571,831).…”
Section: Characteristics Of Atp-dependent Hpr Phosphorylationmentioning
confidence: 99%
“…(x) Effects of hprK mutations alter growth independently of their effects on CR (22). (xi) Several reports have demonstrated the existence of CcpA-independent CR in B. subtilis (7,8,64,73,78,80).…”
Section: Vol 187 2005 Catabolite Repression and Activation In B Sumentioning
confidence: 99%
“…By contrast, Lys160Ala and Lys160Arg substitutions in M. pneumoniae HprK/P led to a complete loss of the two activities (47). Several other mutations affecting amino acids in the P-loop of B. subtilis HprK/P reduced or abolished both catalytic activities (21). The replacement of Gly160 with a serine in L. casei HprK/P, while reducing the phosphorylase activity, had little effect on the kinase activity (38) and yielded a phenotype similar to that observed for mutations affecting the central loop.…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…The so-called capping motif (15), an unusual structure corresponding to the conserved HprK/P signature sequence (43), completes the globular core of the HprK/P subunit. Mutations affecting amino acids in the signature sequence of HprK/P from M. pneumoniae and B. subtilis abolished the dephosphorylation activity, and some also reduced the phosphorylation activity (21,47).…”
Section: Three-dimensional Structure Of Hprk/pmentioning
confidence: 99%